Minds and machines: evaluating the feasibility of constructing an advanced artificial intelligence - Konstantinos Sgantzos; Spyridon Stelios; Panagiotis Tzavaras; Kostas Theologou (Discover Artificial Intelligence)
Abstract It is a popular hypothesis for researchers worldwide that if we manage to construct a lifelike intelligence that depicts most aspects of the human brain, it will be easier for us to understand our own existence. This discussion often ends up in polemic altercations between philosophers, neuroscientists, and technologists on the definition of intelligence. It has also been a subject of interest in both academic and industrial societies, with two prominent concepts emanating at the peak of it, often as one and the same: Artificial Intelligence and Natural Intelligence. While these terms are often used interchangeably, we theorize that they represent two totally distinct and often contradictory constructs. This work aims to portray the most significant divergences between Artificial Intelligence and Natural Intelligence and find out if those can converge under the current technological advancements. We focus primarily on their accurate definitions, then their inner workings, and their potentials and limitations enumerating in the process relative sociological and ethical consequences. Finally, we show why under the current methods the probability of creating an advanced form of Artificial Intelligence is minimal.